ANALISIS PELAYANAN PUBLIK DI PUSKESMAS LAIS KABUPATEN BENGKULU UTARA DI TINJAU DARI INDEKS KEPUASAN MASYARAKAT - Budiman Sakti (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
Health is a state investment in the field of human resources, so that all citizens have the right to their health because it is protected by the constitution as stated in the second paragraph of the 1945 Constitution Article 27 which reads, every citizen has the right to work and a decent living for humanity. It must be admitted that the quality of public health in North Bengkulu Regency, especially in Lais District, has so far been inadequate. People with education and low/poor incomes tend to pay less attention to health factors, their lack of understanding of the importance of health factors in life so that public understanding of the importance of health problems is still often neglected. By understanding the problems faced in this study, the objectives to be achieved are to know and understand how the Community Satisfaction Index (IKM) at the Lais Bengkulu Utara Nursing Health Center and overcome the obstacles faced to increase the Community Satisfaction Index (IKM) at the Lais Bengkulu Utara Nursing Health Center. The sample used in this study was 100 people who came and received treatment at the Lais Nursing Health Center which were determined by accidental sampling research techniques, data were obtained by interview, observation, and questionnaire methods based on the IKM calculation from KEPMENPAN Number 25 of 2004, by calculating 14 service indicators. studied in each element of IKM. The results of the study were found to be in the "Good" category, there were only 2 indicators of the IKM value with the poor IKM category, namely the discipline of service officers and the speed of service officers with a C value or the performance of the service unit "Poor". The main obstacle to increasing the Community Satisfaction Index (IKM) at the Lais Nursing Health Center is the limited budget, lack of medical personnel and medical support. Efforts made by the Lais Nursing Health Center every year are to coordinate with the Health Office, local government, and DPRD to overcome the shortage of medical equipment and human resources.